Scientific Opinion on Polybrominated Diphenyl Ethers (PBDEs) in Food - EFSA Panel on Contaminants in the Food Chain (CONTAM) (EFSA Journal, 2011)
Abstract EFSA was asked by the European Commission to deliver a scientific opinion on polybrominated diphenyl ethers (PBDEs) in food. PBDEs are additive flame retardants which are applied in plastics, textiles, electronic castings and circuitry. PBDEs are ubiquitously present in the environment and likewise in biota and in food and feed. Data from the analysis of 19 PBDE congeners in 3,971 food samples were provided to EFSA by 11 European countries. Eight congeners were considered by the Panel on Contaminants in the Food Chain (CONTAM Panel) to be of primary interest: BDE‐28, −47, −99, −100, −153, −154, −183 and −209. The highest dietary exposure is to BDE‐47 and −209. Toxicity studies were carried out with technical PBDE mixtures or individual congeners. Main targets were the liver, thyroid hormone homeostasis and the reproductive and nervous system. PBDEs cause DNA damage through the induction of reactive oxygen species. The Panel identified effects on neurodevelopment as the critical endpoint, and derived benchmark doses (BMDs) and their corresponding lower 95 % confidence limit for a benchmark response of 10 %, BMDL10s, for a number of PBDE congeners: BDE‐47, 309 μg/kg b.w.; BDE‐99, 12 μg/kg b.w.; BDE 153, 83 μg/kg b.w.; BDE‐209, 1,700 μg/kg b.w. Due to the limitations and uncertainties in the current database, the Panel concluded that it was inappropriate to use these BMDLs to establish health based guidance values, and instead used a margin of exposure (MOE) approach for the health risk assessment. Since elimination characteristics of PBDE congeners in animals and humans differ considerably, the Panel used the body burden as starting point for the MOE approach. The CONTAM Panel concluded that for BDE‐47, −153 and −209 current dietary exposure in the EU does not raise a health concern. For BDE‐99 there is a potential health concern with respect to current dietary exposure.